ELECTRONIC HUMAN RESOURCE MANAGEMENT A SYSTEMATIC LITERATURE REVIEW - Tanuatmodjo, Heraeni (Journal of Business Management Education (JBME), 2021)
Human resource is the basic asset to build a company that needs to be improved and managed, so that the goals set by the company can be achieved properly. The world changing into the industrial revolution 4.0 requires an appropriate information technology. Hence, in order to fulfil the organizational needs for qualified, competent, and committed employees, an electronic Human Resource Management (e-HRM) system is needed to face the challenge in the era of industrial revolution 4.0. The implementation of e-HRM gives benefits in terms of cost savings, time and energy efficiency, flexibility, and long-term growth. However, it has not been proven that a reduction in the number of employees showed savings in costs since there were some technical problems including internet network, less attractive designs, complexities in operating the application, and the strong influence of traditional culture in carrying out duties and jobs by employees.Â  Â Keywords: electronic Human Resource Management